The quest for the missing plastics: Large uncertainties in river plastic export into the sea. (1st November 2022) - Roebroek, Caspar T.J.; Laufkötter, Charlotte; González-Fernández, Daniel; van Emmerik, Tim
Abstract: Plastic pollution in the natural environment is causing increasing concern at both the local and global scale. Understanding the dispersion of plastic through the environment is of key importance for the effective implementation of preventive measures and cleanup strategies. Over the past few years, various models have been developed to estimate the transport of plastics in rivers, using limited plastic observations in river systems. However, there is a large discrepancy between the amount of plastic being modelled to leave the river systems, and the amount of plastic that has been found in the seas and oceans. Here, we investigate one of the possible causes of this mismatch by performing an extensive uncertainty analysis of the riverine plastic export estimates. We examine the uncertainty from the homogenisation of observations, model parameter uncertainty, and underlying assumptions in models. To this end, we use the to-date most complete time-series of macroplastic observations (macroplastics have been found to contain most of the plastic mass transported by rivers), coming from three European rivers. The results show that model structure and parameter uncertainty causes up to four orders of magnitude, while the homogenisation of plastic observations introduces an additional three orders of magnitude uncertainty in the estimates. Additionally, most global models assume that variations in the plastic flux are primarily driven by river discharge. However, we show that correlations between river discharge (and other environmental drivers) and the plastic flux are never above 0.5, and strongly vary between catchments. Overall, we conclude that the yearly plastic load in rivers remains poorly constrained. Graphical abstract: Image 1 Highlights: Plastic transported to the ocean through rivers is poorly captured in models. Discharge under normal conditions is a poor predictor for plastic in rivers. Uncertainty in riverine plastic estimates is very large and generally underestimated.